PENETAPAN KADAR METANOL HASIL DESTILASI PENGUAP VAKUM PUTAR EKSTRAK METANOL DAUN UBI UNGU MENGGUNAKAN RAMAN SPEKTROFOTOMETER - Dewi, Santi Maha (Jurnal Farmasi Udayana, 2018)
Solvent extracted results are often not utilized for re-extraction. Methanol is a universal solvent which is often used as an extract of simplicia. The result of a rotary vacuum evaporator distillation is not known purity and level. Raman spectrosphotometer is a non destructive method of analysis that can be applied to determine the levels and purity of distilled methanol. The objective of this research is to know the change of vacuum pressure to the level and purity of methanol, so that methanol from rotary vacuum distillation can be reused for re-extraction. Purple sweet potato leaves are macerated using 95% methanol : 3% citric acid. The extract was evaporated using a rotary vacuum evaporator at 100 mbar, 150 mbar, and 200 mbar vacuum pressure with a range of 5 to 180 min. Purity and methanol levels were determined using a Raman Handheld 1064 nm spectrophotometer. Validation of methanol assay method with Raman spectrophotometer was obtained: precision: KV 0.19% -1.70%, accuracy: 94.4-103.8%, limit of detection: 1.77% (v/v), limit of quantification: 5.89% (v/v), the range of linearity of 1.77% -99.9% (v/v), with a calibration curve equation: y = 216,88x + 1437.1 and the value of R 2 = 0.9997. Methanol content of distillation product with pressure variation 100 - 200 mbar in the span of 5 to 180 minutes obtained methanol level 59.8-81.2% (v/v). All distilled methanol yields a spectrum similarity of 86-99% when compared with absolute methanol.